2′-19F labelling of ribose in RNAs: a tool to analyse RNA/protein interactions by NMR in physiological conditions - Kara, Hesna; Axer, Alexander; Muskett, Frederick W.; Bueno-Alejo, Carlos J.; Paschalis, Vasileios; Taladriz-Sender, Andrea; Tubasum, Sumera; Vega, Marina Santana; Zhao, Zhengyun; Clark, Alasdair W.; Hudson, Andrew J.; Eperon, Ian C.; et al. (Frontiers in Molecular Biosciences, 2024)
Protein-RNA interactions are central to numerous cellular processes. In this work, we present an easy and straightforward NMR-based approach to determine the RNA binding site of RNA binding proteins and to evaluate the binding of pairs of proteins to a single-stranded RNA (ssRNA) under physiological conditions, in this case in nuclear extracts. By incorporation of a 19 F atom on the ribose of different nucleotides along the ssRNA sequence, we show that, upon addition of an RNA binding protein, the intensity of the 19 F NMR signal changes when the 19 F atom is located near the protein binding site. Furthermore, we show that the addition of pairs of proteins to a ssRNA containing two 19 F atoms at two different locations informs on their concurrent binding or competition. We demonstrate that such studies can be done in a nuclear extract that mimics the physiological environment in which these protein-ssRNA interactions occur. Finally, we demonstrate that a trifluoromethoxy group (-OCF3) incorporated in the 2' ribose position of ssRNA sequences increases the sensitivity of the NMR signal, leading to decreased measurement times, and reduces the issue of RNA degradation in cellular extracts.